Guardianship of Diffuse Assets and Private Relations - Queiroz, Fernanda Dayane dos Santos (2019)
Brazil is the stage for being a Universal State of Law, in which citizens use the universal instrument, be it their right to vote, to define, by majority, who will be the representatives of the next 04 or even 08 years. More in the face of this political panorama, where there are issues such as corruption and the absence of a clause to increase the risk of risk capital. To do this, using qualitative bibliographical research, it is intended with this opinion to evaluate the foundation that permeates the notions of suffrage, democracy and vote, highlighting the importance ofÂ a broad awareness prior to any change in a regime is not a Brazilian cultural problem. Moreover, it is intended with this article to select a supremacy of the vital vow of some aspect and, in general, it is a vital force that is at will and its followers of sovereignty in the democratic state. Finally, it is intended that, historically, Brazil and its organizations do not promote the individual the full development of the human personality. Thus, (in) the viability of the optional or incremental vote of (morality), the possibility of annulment of the lower areas of Brazilian society. This is an elementary works proposed by present article.